Discussion: wrestling with the beast - Short, James F. (Crime, law and social change, 2006)
Criminology is but one of what Abbott refers to as "sociologies archipelago of particular subject matters." I discuss the papers in this issue of Crime, Law and Social Change as "fractals" of disciplines that contribute to knowledge in criminology.